0304 Leg Movements In Sleep (LMS) Post-Stroke Compared To Healthy Adults Occur More Commonly Related To Stroke Location And Differing From Classical Periodic Leg Movements Of Sleep (PLMS). (27th April 2018) - Mudumbi, S; Wang, A; Earley, C J; Allen, R P
Abstract: Introduction: Stroke alters cortical disinhibition/excitability affecting motor control presumably increasing LMS. This study evaluates all LMS with durations accepted for PLMS (0.1 to 10s) for affected and unaffected side of early-phase stroke patients compared to matched controls Methods: LMS from leg activity meters were obtained on 11 patients 3–19 days post stroke and 10 age and gender-matched controls. Average NIH stroke severity scale was 9.7 ± 4(range 4–18). Records were scored using revised PLM criteria that end a run of LMS whenever the inter-movement interval between onsets (IMI) is too short. This avoids erroneously accepting many closely spaced LMS with too short IMI as classical PLMS. Results: The number and the standard deviation of durations of LMS with short IMI (<10 seconds) for stroke patients were larger but PLMS/hr with IMI >10, < 90 seconds did not differ compared to control. The difference between unaffected and affected sides in LMS/hr with IMI<10 s was high in cortical and subcortical stroke and minimal in brainstem stroke Conclusion: LMS observed post-stroke are not typical PLMS in their characteristics nor is the density of PLMS significantly greater than normal healthy adults. Numbers of LMS packed closely together (onsets<10 s apart) are both excessive and more on the unaffected than affected side for cortical and subcortical but not brainstem stroke. These assessments of LMS with short intervals between onsets may provide objective motor output measures of disinhibition/excitability reflecting neural plasticity relevant for post-stroke recovery. Support (If Any): Gift account.